Il paesaggio figurato (2018)
Drawing is a powerful form of communication, and it can activate the imagery. This volume discusses two themes: the representation of landscape, where the image is used for descriptive purposes, and the prefigurement of landscape, where drawing is the tool for the definition of scenes. The two actions are closely related. Outlining the structure of the landscape (for which the bird's eye view appears to be an effective representation) enables the deduction of the constitutive and evolutionary rules which necessarily lead to the identification of the rules of good behaviour for the preservation and transformation of the landscape. Drawing these action guidelines can help aim the transformations, as it allows the simple and straight communication of the ways in which it is possible to intervene in our common living environment.